The use of visual diary in understanding art history and culture / Afza Arrmiza Razif - Razif, Afza Arrmiza (2015)
This study aimed on implementing the use of Visual Diary in an art classroom to learn Art History and Culture about the Mah Meri tribe. The purpose is to make Art students easier to understand and memorize Art History facts. This looked at the Visual Art Education students’ perception and views on the use of Visual Diary as an effective medium in understanding about the Mah Meri Culture. A survey, questionnaire and descriptive research was conducted to collect the data regarding this study. In this study, the respondents chosen were seventeen Visual Art Education post graduate students who took PSV 712 course, Art and Visual Studies. Based on the findings, this study showed that most students agreed with the use of Visual Diary as an effective medium in understanding Mah Meri Culture. From the findings also, it can be concluded that by combining the information collected together with creativity, students were able to report a detail understanding of Mah Meri tribe in their own Visual Diary. On the whole result of findings proved that Visual Diary has potentials to be used as a teaching medium in learning Art History and Culture.